The essence and prospects of studying journalism of the Stalin era [Book review: Zhirkov G.V. Journalism of the Stalin era. 1928 − the 1950s] - A.Sh. Bik-Bulatov; D.V. Tumanov (Ученые записки Казанского университета: Серия Гуманитарные науки)
-